PERBEDAAN MODEL OHLSON, MODEL TAFFLER DAN MODEL SPRINGATE DALAM MEMPREDIKSI FINANCIAL DISTRESS - Anny Widiasmara; Henny Catur Rahayu (INVENTORY: JURNAL AKUNTANSI, 2019)
The purpose of this study is to provide empirical evidence that there are differences in the Ohlson, the Taffler and the Springate Model in predicting financial distress for companies listed on the Indonesia Stock Exchange in 2015-2017. The population in this study are all nine industrial sector companies listed. This study uses secondary data from annual financial reports / annual report in 2015-2017. Testing the hypothesis in this study using the normality test and the Kruskal Wallis test (different test). The results showed that the Taffler model is the model that has the highest level of accuracy in predicting financial distress conditions of companies listed on the Stock Exchange with an accuracy rate of 83.93%, then the Springate Model with an accuracy rate of 54.91% and the Ohlson Model which is a model with the lowest accuracy rate is 6.70%.Keywords: Ohlson Model, Taffler Model, Springate Model, Financial Distress